Student's Need Analysis for the Development of Chemistry Modules Based Guided Inquiry to Improve Science Process Skill - Arantika, Jane; Saputro, Sulistyo; Mulyani, Sri (International Journal of Pedagogy and Teacher Education, 2018)
Science process skills (SPS) are an important aspect of learning science. SPS help students to develop creativity in learning. Process skills such as observing, formulating questions, interpreting, experimenting, hypothesizing, applying concepts, and communicating. This study aims to analyze the need for development resources needs of science filled with science process skills. Requirement analysis of the development of teaching materials with the skill of the process of science needs to be done because the textbook is the reference a teacher in the class. The subjects matter of chemistry the study was three senior high schools in Sambas, West Borneo. Needs analysis conducted using a qualitative approach, in terms of needs in classroom learning and content of process skills on teaching materials. Data were collected by interviews and questionnaires were analyzed descriptively. The results showed that as many as 27 percents of students perceive the book used in learning has not yet trained the science process skills. As many as 73 percents of students perceive that they need instructional materials in the form of inquiry-based chemistry modules to improve science process skills. Modules are developed based guided inquiry for having guided inquiry learning stages that can practice students' science process skills.